14 Enhanced supportive care – joint working between supportive care and acute oncology to deliver rapid access to expertise. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Mola, Lisa La; Campbell, Geraldine; Berman, Richard; Cooksley, Tim; Al-Sayad, Tamar; Clare, Hannah
Abstract : The Enhanced Supportive Care (ESC) clinic provides patients with better access to supportive care services. It allows any Christie patient with problems relating to their cancer, or cancer treatment, to be seen without delay. This helps to reduce the escalation of symptoms and medical problems that could potentially lead to hospital admission. ESC clinic is a new joint service provided by Supportive Care and Acute Oncology teams. A six month pilot has demonstrated a reduction in emergency admissions to the Christie, a reduction in patients sent elsewhere within Greater Manchester (GM), a reduction in the need for GP follow up appointments, reduced length of stay and has facilitated early discharges from the Oncology Assessment Unit (OAU), which improves patient flow. Referrals into the ESC clinic are received from multiple areas, namely: Acute Oncology Management Service/Hotline Oncology patients from Outpatient areas Radiotherapy treatment areas Oak Road Treatment Centre. Community Macmillan direct referrals A bespoke proforma was completed after each consultation by the treating clinician. 413 ambulatory patient reviews took place over a 6 month period. An in depth analysis has been conducted of 236 new patient referrals between January and June 2017. Overall results show a significant impact on patient outcomes, with 21% avoided admissions, 25% facilitated early discharge and 43% avoided escalation of symptoms/GP review. Data analysis remains on going to assess readmission statistics; in particular an analysis of early OAU discharges, facilitated by the ESC clinic review of low risk neutropenic patients. The service currently operates two clinics a week on Monday and Thursday afternoons. A business case has been submitted proposing service expansion to operate daily clinics. As the first cancer centre to implement this service, we have welcomed oncology teams from other centres across the UK, enhancing practice elsewhere.